Reversal of anticoagulant effects of edoxaban, an oral, direct factor Xa inhibitor, with haemostatic agents - Fukuda, Toshio; Honda, Yuko; Kamisato, Chikako; Morishima, Yoshiyuki; Shibano, Toshiro (Thrombosis and haemostasis, 2012)
Edoxaban, an oral, direct factor Xa inhibitor, has a similar or low incidence of bleeding events compared with other anticoagulants in clinical trials. Therefore, agents to reverse the anticoagulant effects of edoxaban could be desirable in emergency situations. In this study, the reversal effects of haemostatic agents were determined on prothrombin time (PT) prolongation in vitro and bleeding time prolongation in vivo by edoxaban. PT using human plasma was measured in the presence of edoxaban at therapeutic and excess concentrations with the haemostatic agents, prothrombin complex concentrate (PPSB-HT), activated prothrombin complex concentrate (Feiba), and recombinant factor VIIa (rFVIIa). In rats, rFVIIa and Feiba was given during intensive anticoagulation with edoxaban. The haemostatic effect was evaluated in a model of planta template bleeding and a potential prothrombotic effect was evaluated in a venous thrombosis model. PPSB-HT, Feiba, and rFVIIa concentration-dependently shortened PT prolonged by edoxaban. Among these, rFVIIa and Feiba showed potent activities in reversing the PT prolongation by edoxaban. rFVIIa (1 and 3 mg/kg, i.v.) and Feiba (100 U/kg, i.v.) significantly reversed edoxaban (1 mg/kg/h)-induced prolongation of bleeding time in rats. In a rat venous thrombosis model, no potentiation of thrombus formation was observed when the highest dose (3 mg/kg) of rFVIIa was added to edoxaban (0.3 and 1 mg/kg/h) compared with the control. The present study indicated that rFVIIa, Feiba, and PPSB-HT have the potential to be reversal agents for edoxaban.